Consultancy work for vibration testing and human comfort criteria assessment / Goh Lyn Dee - Goh, Lyn Dee (Unit Penerbitan FKAPP, 2019)
This project was headed by Dr. Goh Lyn Dee from the Faculty of Civil Engineering UiTM Cawangan Pulau Pinang with a collaboration with Smart Sensing Technology Sdn. Bhd. and a team from Faculty of Civil Engineering, Universiti Tun Elussein Onn, to investigate the vibration issue at a four storey office building. The users in the building were complaining that they felt uneasy/dizziness when there were human activities on the affected areas as the floor vibrated even an average weight man was walking on the floor. Thus, the vibration testing was proposed to determine the vibration behaviour of the floor slabs and the human comfort criteria was assessed. There were three types of tests conducted at the site; i.e. the ambient tests, the shaker tests and the walking tests. To capture the responses of the floor in all directions during the tests, the accelerometers were installed in all directions.